Metode Kajian Islam Secara Rasional Dalam Ilmu Sosial - Maisarotuzzuhra (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2025)
Research methods in social sciences play a crucial role in research, enabling researchers to collect accurate and relevant data. Various methods, such as observation, interviews, and document analysis, are used to answer research questions. The appropriate selection of methods significantly impacts the validity and reliability of research findings. A deep understanding of research methods helps researchers produce trustworthy findings and avoid bias. Using suitable methods makes the research process more accurate and findings more valid, making a meaningful contribution to social sciences. A rational approach in Islamic and social science studies supports objectivity, helps researchers identify patterns in social phenomena, and make relevant generalizations. This approach also avoids bias and subjective perceptions, ensuring that research results are accountable. Rational Islamic studies allow for adapting religious teachings to modern developments, maintaining fundamental values while remaining relevant. Thus, collaboration between religion and social sciences yields broader and more inclusive understanding, supporting the development of a just and harmonious society. The application of these methods, such as in zakat management, demonstrates the positive contribution of social sciences in improving community welfare. Evaluating social programs by Islamic institutions through rational methods ensures significant and targeted benefits, strengthening collaboration with the government. With a rational approach, research can produce more inclusive public policies, enhance social justice, and make significant contributions to social sciences. This research has the potential to provide tangible benefits to society and serve as a foundation for subsequent studies, creating a broader positive impact on the development of social science knowledge.